Persentase Serangan dan Kerusakan Hama Penggerek Batang (Hexamitodera semivelutina Hell.) pada Tanaman Cengkeh (Syzygium aromaticum L.) Berdasarkan Ketinggian Tempat di Kabupaten Minahasa (JURNAL ENFIT : Entomologi dan Fitopatologi, 2023)
One type of plant disrupting organism that attacks clove plants is the clove stem borer. Hexamitodera semivelutina Hell. which is the main pest of clove plants in North Sulawesi.  The study aimed to determine the percentage of attack and damage to clove plants from clove stem borer, H. semivelutina based on altitude in Minahasa Regency.  The research was conducted using survey method.  The observation location was divided into three altitude ranges from sea level, namely: altitude range 0-300 meters above sea level, altitude 301-600 meters above sea level and altitude 601-900 meters above sea level. The things observed were the percentage of H. semivelutina attack and damage to clove stems measured through the number of burrows. The results showed that the percentage of H. semivelutina infestation in Koha Village at an altitude of 0-300 m above sea level ranged from 73.30 - 93.30% with an average of 83.30%; Agotey Village 301-500 m above sea level ranged from 56.60 - 100.00% with an average of 78.30% and Eris Village 501-900 m above sea level ranged from 83.30 -100.00% with an average of 89.30%.  Damage to clove stems by the pest H. semivelutina in Koha Village with an altitude of 0-300 m above sea level obtained the results of active burrows 34-46 burrows with an average of 38.25 burrows and inactive burrows 40-55 burrows with an average of 47.25 burrows; Agotey Village at 301-500 m asl, active burrows 25-49 burrows with an average of 35.00 burrows and inactive burrows 34-57 burrows with an average of 45.75 burrows; and Eris Village at 501-900 m asl, active burrows 30-49 burrows with an average of 36.25 burrows and inactive burrows 36-56 burrows with an average of 43.50 burrows.